Grafting of Different Monomers onto Nano Aluminum Surface and Studying Their Biological Activities - Sultan, Maha Taher; Atwan, Zainab Khalaf (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
The research includes the preparation of two nano polymer (   ,    ) through a grafted nano ceramic material (aluminum oxide      )(80 nm) by acrylic acid monomer. The latter was extended with two different ester monomers using free radical polymerization. The antibacterial activity of the prepared compounds) performed according to the agar diffusion method.  All compounds (1, 2, 3, 4, NP1, NP2) showed inhibition against bacterial